2022
DOI: 10.1111/hel.12929
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori infection and its eradication on the expression of tight junction proteins in the gastric epithelium in relation to gastric carcinogenesis

Abstract: Background Tight junction proteins (TJPs) play a role in epithelial defense mechanisms. However, the effect of Helicobacter pylori (Hp) on TJPs remains unclear. This study aimed to evaluate the expression of TJPs in relation to Hp infection and eradication in gastric carcinogenesis. Methods In total, 510 subjects (284 controls and 226 gastric cancer [GC] patients) were prospectively enrolled in the study. The expression of claudin‐1 and ‐2 (CLDN‐1, ‐2), occludin (OCLN), and tight junction protein 1 (TJP1) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Additionally, HFD-induced obesity reduces Ileibacterium spp., and the abundance of these bacteria is negatively correlated with chronic in ammatory diseases such as obesity, atherosclerosis, and aging [40][41][42]. It has been reported that Helicobacter negatively correlates with intestinal tight junction protein expression, which increases after HFD feeding [43]. Furthermore, we described the association between HFD-induced obesity and controversial Helicobacter, whose abundance did not increase signi cantly after HFD feeding [44,45].…”
Section: Discussionmentioning
confidence: 67%
“…Additionally, HFD-induced obesity reduces Ileibacterium spp., and the abundance of these bacteria is negatively correlated with chronic in ammatory diseases such as obesity, atherosclerosis, and aging [40][41][42]. It has been reported that Helicobacter negatively correlates with intestinal tight junction protein expression, which increases after HFD feeding [43]. Furthermore, we described the association between HFD-induced obesity and controversial Helicobacter, whose abundance did not increase signi cantly after HFD feeding [44,45].…”
Section: Discussionmentioning
confidence: 67%
“…This retrospective study assembled a cohort of 474 subjects who underwent magnetic-controlled capsule endoscopy coupled with a 13 C urea breath test at the Digestive Endoscopy Center, Children's Hospital a liated with Shanghai Jiao Tong University School of Medicine, spanning January through December 2023. Inclusion criteria encompassed individuals aged 6-18 who had the 13 C urea breath test conducted within a fortnight before or after magnetic-controlled capsule endoscopy. Exclusion criteria included those previously treated for HP infection or those administered proton pump inhibitors, bismuth compounds, or antibiotics within one month prior to the 13 C urea breath test; subjects with a history of gastric surgery; patients with past or present gastric or duodenal ulcers; and cases with incomplete data.…”
Section: Study Populationmentioning
confidence: 99%
“…Diagnosis of Helicobacter pylori (HP) infection within the study cohort was ascertained using the 13 C urea breath test. Participants manifesting positive results were a rmed to harbor HP infection, while those yielding negative outcomes, devoid of any antecedent HP eradication interventions, were adjudged HP-negative.…”
Section: Hp Diagnosismentioning
confidence: 99%
“… 9 TME is related to chronic inflammation and Helicobacter pylori infection of the gastric epithelium is a major risk factor for GC. 10 H. pylori -associated gastritis could promote TME including destruction of tight junction protein. 10 This is supported by the beneficial effects of H. pylori eradication in reducing the risk of primary GC incidence 11 , 12 and prevention effect of metachronous GC with a hazard ratio (HR) of 0.32 (95% confidence interval [CI], 0.15 to 0.66; p=0.002).…”
Section: Introductionmentioning
confidence: 99%
“… 10 H. pylori -associated gastritis could promote TME including destruction of tight junction protein. 10 This is supported by the beneficial effects of H. pylori eradication in reducing the risk of primary GC incidence 11 , 12 and prevention effect of metachronous GC with a hazard ratio (HR) of 0.32 (95% confidence interval [CI], 0.15 to 0.66; p=0.002). 13 Therefore, we hypothesized that the risk factors and survival rates of SMGC are different from those of single GC.…”
Section: Introductionmentioning
confidence: 99%